Channeling Good Images but Not Substantive Blessings? Education and Social Contact on Pro-Migrant Sentiments in an Internal Migration Setting. (4th November 2021) - Tong, Yuying; Nie, Tianzhu; Piotrowski, Martin
Abstract: Education and intergroup contact are two of the most influential channels for reducing host society members' hostility toward immigrants, but recent studies suggest that these two channels are only able to shift their impressions. Yet, a shift in impression does not necessarily translate into endorsement of integration policies, resulting in a "principle-policy paradox" in multiracial societies. Little is known about whether this paradox holds in circumstances where racial boundaries are less salient and rigid. In this study, we examine whether such a paradox exists in urban China, where racial/ethnic hostility is negligible but the Hukou system has created institutional segregation between local residents and migrants. Using data collected from twelve middle-size cities and one metropolis, we examine urban residents' attitudes toward rural migrants from multiple domains. We find that education is positively associated with locals' positive judgments about rural migrants, with concern about social justice playing a mediating role. However, there is a lack of association between education and the endorsement of integration policy or social distance. Compared with education, social contact, in particular kinship contact, is associated with support in more substantive domains, ranging from integration policies to a closer social distance. Nevertheless, social contact does not lead to the support for the most pivotal policy change of granting Hukou . The findings indicate that both education and social contact are limited in engendering the extension of benefits to migrants across contexts, but intergroup contact is more capable of doing so in a society with a more fluid group boundary.